2012
DOI: 10.4081/ijas.2012.e22
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary studies on hoof characteristics in Amiata donkey

Abstract: In this work the biometrical, physical and chemical characteristics of Amiata donkey hoof were studied. The Amiata donkey is a local endangered breed and derives from the homonym mountain in Tuscany. This donkey, which was once used as pack animal in farms and in mines, is now involved in trekking, onotherapy and milk production. The mean hoof biometrics and its standard deviation were calculated. The physical and chemical characteristics were also estimated, through ANOVA, considering the hoof region as fixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 13 publications
4
19
1
1
Order By: Relevance
“…The characteristics of coat color and healthy hooves found in this study confirmed the findings of previous studies concerning morphology and hoof characteristics of Amiata donkey (Sargentini et al, 2009;2012). As already stated by the same authors (Sargentini et al, 2009), signs on legs (stripes and zippers) seem to be a peculiar trait of the breed, whereas dovetail and neck buttons are less representative.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The characteristics of coat color and healthy hooves found in this study confirmed the findings of previous studies concerning morphology and hoof characteristics of Amiata donkey (Sargentini et al, 2009;2012). As already stated by the same authors (Sargentini et al, 2009), signs on legs (stripes and zippers) seem to be a peculiar trait of the breed, whereas dovetail and neck buttons are less representative.…”
Section: Discussionsupporting
confidence: 92%
“…The breed was used in the past as a pack animal on farms and in mines, which are rather diffused in this area. The Amiata donkey is now used for milk production (Martini et al, 2014;Ragona et al, 2016), onotherapy (Camillo, 2011), and trekking (Sargentini et al, 2009;2012). This breed can also valorize marginal and minor historical and touristic sites through the transport of materials and garbage collection (Sargentini et al, 2009;2012).…”
Section: Introductionmentioning
confidence: 99%
“…Although little information exists on the effect of cold stress on the donkey (Ayo et al, 2013), thermal stress in dairy animals negatively affects the quantity and quality of milk (Bernabucci et al, 2010). Moreover, some features of the Amiata breed, such as the scapular cross and the zebra stripes, suggest that it descended directly from the African donkey (Sargentini et al, 2012); thus, the Amiata origin would indicate good adaptation to a warm climate.…”
Section: Short Communicationmentioning
confidence: 95%
“…The average concentrations of some elements presented certain deviation from the published data, which also varied for each other (Tocci et al, 2015;Sargentini et al, 2012;Faria et al, 2005). This difference may be associated with the methodology used in each experiment, associated with variables that influence the quality of the hoof.…”
Section: Discussionmentioning
confidence: 90%
“…Studies have been conducted to investigate the chemical composition of horses and donkeys hooves, but there are still few and not enough to help in the indication of strategies that improve the quality of the hooves of the animals (Faria et al, 2005;Sargentini et al, 2012;Tocci et al, 2015). Thus, this study aimed to determine and compare the concentrations of sodium, potassium, copper, iron, zinc, magnesium and calcium in different regions of the hoof and between pigmented and non-pigmented hooves of horses, mules and donkeys.…”
Section: Introductionmentioning
confidence: 99%